Społeczeństwo według "Faktu" - próba charakterystyki - Czajka-Bubniak, Anna (Słowo. Studia językoznawcze, 2014)
The article presents a reconstruction of the world created in the tabloid’s reality by the language. Research are based on the Karpman’s dramatic triangle assumed existence of three social roles: victim, persecutor and savior. The creation of the social forms is made by the repetition of particular words: shock, scandal, sensation, horror, alarm, attention, swindle. The tabloid’s addressee is rather little choosy, simple and accept the primitive world, bad or good, black or white. The words’ repetition is causing formation some typical stereotypes in tabloid and in the society.